(untitled) (Faridpur Medical College Journal, 2021)
Prematurity is one of the major causes of neonatal death in developing countries like Bangladesh. Appropriate protocol for nutritional support of the preterm infants is essential to achieve a postnatal growth rate similar to that of a normal fetus. Objective of the study was to assess the effects of the existing nutritional support protocol of Bangabandhu Sheikh Mujib Medical University (BSMMU) in the early postnatal growth velocity of the preterm infants.This quasi-experimental study was conducted in the Department of Neonatology, BSMMU, Bangladesh from January to December 2015. All admitted infants aged <48 hours and born <_32 weeks of gestational age were included in this study. Infants were provided with nutritional support as per the BSMMU feeding guideline. The subsequent growth of the children was followed up routinely to measure the growth velocity. Of the 38 infants of our study, the mean calorie intake was 66.71 Kcal/kg/day. Overall mean growth velocity of weight, length and occipitofrontal circumference (OFC) up to discharge were 8.97 g/kg/day, 0.85 cm/week, and 0.41 cm/week respectively. Very low birth weight (VLBW) infants got significantly more calories compared to low birth weight (LBW) infants (p = 0.009). Mean growth velocity in weight of LBW infants were 8.18 g/kg/day and VLBW were 9.95 g/kg/day (p = 0.233). At birth, only 2.6% of infants had weight <10th centile, but at discharge, it was 52.6%. Early postnatal nutritional supplementation was not adequate, and postnatal growth failure remains very high in the hospital admitted preterm infants. Faridpur Med. Coll. J. 2020;15(2): 79-84